2022
DOI: 10.1186/s12917-022-03546-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and phenotypic diversity of Prototheca spp. recovered from bovine mastitis in terms of antimicrobial resistance and biofilm formation ability

Abstract: Background The Prototheca algae have recently emerged as an important cause of bovine mastitis globally. Isolates from bovine mastitis in several countries were nearly all identified as P. bovis, suggesting that it was the main causative agent of bovine protothecal mastitis. The aim of the present study was to evaluate the presence and isolation of Prototheca spp. in dairy farms, detect the genetic diversity among strains, determine the capacity of producing biofilm and their resistance to anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A recent taxonomic reclassification of the algae in 14 species has been proposal based on mitochondrial cytB gene, where P. bovis and, less frequently, P. blaschkeae, are recognized as the main algae-related bovine mastitis species worldwide [43], including in Brazil [44,45]. Nonetheless, to date, none therapeutic protocol has been considered effectiveness to treat protothecal mammary infections [46], which has motivated a set of in vitro studies evaluating the algaecidal effect of different compounds, including antimicrobials, antifungal, sanitizer, natural extracts, essential oils, nanoparticles, and herbicides [44,47,48]. In the current study, 2.6% of cultured milk samples revealed isolation of the genus Prototheca, a fact that is concerning, due to absence of specific treatment approaches and, at this moment, the control [42,43] measures against this alga have been restrict to segregation, chemical dry of quarters, and culling of infected cows [42,43,48].…”
Section: Discussionmentioning
confidence: 99%
“…A recent taxonomic reclassification of the algae in 14 species has been proposal based on mitochondrial cytB gene, where P. bovis and, less frequently, P. blaschkeae, are recognized as the main algae-related bovine mastitis species worldwide [43], including in Brazil [44,45]. Nonetheless, to date, none therapeutic protocol has been considered effectiveness to treat protothecal mammary infections [46], which has motivated a set of in vitro studies evaluating the algaecidal effect of different compounds, including antimicrobials, antifungal, sanitizer, natural extracts, essential oils, nanoparticles, and herbicides [44,47,48]. In the current study, 2.6% of cultured milk samples revealed isolation of the genus Prototheca, a fact that is concerning, due to absence of specific treatment approaches and, at this moment, the control [42,43] measures against this alga have been restrict to segregation, chemical dry of quarters, and culling of infected cows [42,43,48].…”
Section: Discussionmentioning
confidence: 99%
“…P. bovis is reported to be capable in biofilm production [11,12]. This polymeric matrix is produced by other organisms causing mastitis, such as bacteria and fungi.…”
Section: Pathogenesismentioning
confidence: 99%
“…Conventional antimycotic drugs were in vitro checked against P. bovis [109, [113][114][115], with amphotericin B considered quite efficient, also in the presence of biofilm-producing P. bovis strains [12]. However, in a multicentric study, involving 144 isolates of P. bovis and P. blaschkeae, strong differences in sensitivity to amphotericin B and some azoles were reported based on the geographic source of strains [114].…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The algae thrive in warm, humid environments where there is plentiful organic matter, such as forage, bedding materials, and cattle feces, which has resulted in the frequent infection of dairy cows [ 7 ]. In addition, recent studies showed that P. bovis isolates are susceptible to several antibiotics and antifungal drugs in vitro, but no effective clinical treatment is currently available, making prevention and treatment more difficult [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%